Do Neighbors Help Finding a Job? Social Networks and Labor Market Outcomes After Plant Closures - Elke J. Jahn; Michael Neugart (Institute of Labor Economics (IZA), 2017)
Social networks may affect workers' labor market outcomes. Using rich spatial data from administrative records, we analyze whether the employment status of neighbors influences the employment probability of a worker who lost his job due to a plant closure and the channels through which this occurs. Our findings suggest that a ten percentage point higher neighborhood employment rate increases the probability of having a job six months after displacement by 0.9 percentage points. The neighborhood effect seems to be driven not by social norms but by information transmission at the neighborhood level, and additionally by networks of former co-workers who also lost their jobs due to plant closure.
Keywords: J63; J64; R23; 330; social networks; job search; neighborhood; employment; wages; plant closures